Medical Students and Prevalence of Sleep Disorder Insomnia - Mohsan ul Malik, Muhammad Muzzamal Irshad, Atif Shahzad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of this research is to find out how often medical students suffer from insomnia. Study Design: Descriptive cross sectional study Place and Duration of Study: THQ Hospital Kamalia. Nov 2020-Aug 2021 Methodology: A total of 112 students, both male and female, took part in this study. The demographics of the patients, including their age, gender, BMI, socioeconomic status, and marital status, were documented after receiving a signed permission from all parties. The patients were between the ages of 20 and 38 years old. The Athens Insomnia Scale (AIS) was used to gauge the frequency with which cases suffered from insomnia. The SPSS 24.0 version was used to analyze all of the data collected here. Results: In our study the mean age of the patients was 25.13±8.41 years and mean BMI 22.15±11.31kg/m2. Majority was males 70 (62.5%) and females were 42 (37.5%) patients. Majority were from middle socio-economic status 62 (55.4%) followed by upper class 25 (22.3%) and poor 25 (22.3%). 80 (71.4%) of the patients were single. According to the AIS scale, insomnia was reported by 50 (44.6 percent) of the patients, the majority of whom were female. Conclusion: We concluded that Studying late at night to get good grades resulted in a considerable increase in the prevalence of insomnia among medical students. As one gets older, the likelihood of developing it increases. In addition, it is feasible to lower it to the entire night's sleeping time (7 to 10 hours).